THE IMPACT OF EDUCATIONAL TECHNOLOGY ON THE ACHIEVEMENT IN THE GENERAL SCIENCE SUBJECTS OF THE 6 th GRADE STUDENTS - Abdel-Rahman Arman, Ibrahim Mohd (IJRDO- Journal of Educational Research, 2017)
The purpose of this study was to investigate the impact of educational technology(El-Gazzar's model) on the achievement in the general science subjects of the 6th gradestudents.The sample of the study consisted of (54) students – males and females – from 6thgrade – Abu Deis Coeducation school.The researcher assigned two groups randomly (control and experimental) group.To achieve the objective of the study, the researcher collected information by usinga multiple choice test of (40) items. Students were given pre-test and post.. The test was subjected to validity, reliability, and level of difficulty anddiscrimination measuresThe Data were analyzed by using (SPSS) with ANCOVA, the results showedfollowing:-There was a statistically significant difference at the level (α ≤0.05) in achievementof science due to the method of teaching in favor the group which is experimental, Therewas no statistically significant difference at the level (α ≤0.05) in achievement of sciencedue to the interaction between teaching method and gender.Based on these results the researcher recommends the use of EducationalTechnology (El-Gazzar's Model) in teaching and. especially in teaching science, for thepurpose of raising the level of students' achievement. And performing similar studies onother grades, and other units, with larger groups and samples and in several areas in orderto generalize the results of this study.